PERLINDUNGAN DAN PENEGAKAN HAM DALAM KASUS PELECEHAN SEKSUAL DI INDONESIA - Karomah, Lailatul (Universitas Nurul Jadid, 2025)
Violence against women in Indonesia is still a complex and systematic problem, covering various aspects of life such as family, education, work, social, and politics. Gender inequality rooted in patriarchal culture causes women to be in a more vulnerable position to various forms of violence, whether physical, sexual, psychological, or economic. Gender stereotypes that place women in a subordinate position further exacerbate this condition. Therefore, this research aims to analyse the factors that cause violence against women, the forms of violence that occur, and the effectiveness of legal protection that has been implemented in Indonesia. This research uses a normative juridical method with a legislative approach and case studies to identify weaknesses in the legal protection system for victims. The results show that although there are various national and international legal instruments to protect women, policy implementation still faces various obstacles, including weak law enforcement and low public awareness. As a recommendation, it is necessary to strengthen legal policies that are more pro-victim, increase socialisation of women's rights, and public education to remove social norms that justify gender-based violence. With these steps, it is hoped that the protection of women can be optimised and justice can be realised.